ChemInform Abstract: From Solution to the Solid State: Control of Niobium Oxide—Fluoride [NbOxFy]n‐ Species. Issue 11 (18th March 2014) - Lu, Hongcheng; Gautier, Romain; Donakowski, Martin D.; Liu, Zhengtang; Poeppelmeier, Kenneth R.
Abstract Compounds (II) and (III) are formed by adjusting the acidity of the solution using different organic bases.